Effectiveness of forestry related best management practices in the Trout Creek Watershed, Colorado - Stednick, John D., author; Teves, Nani Bay, author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2005)
In multiuse forests the majority of nonpoint source pollution is typically sediment. Best management practices (BMPs) are implemented to reduce or prevent this pollutant, however little research has been done to quantify the effectiveness of individual types of BMPs. The overall goal of this project was to evaluate the effectiveness of three BMPs implemented to reduce sediment in Trout Creek: cattle fences, off-road vehicle signs, and road culverts. The effectiveness of the combined BMPs in the land use area was evaluated by comparing water quality and Wolman pebble counts with an upstream reference area. The reference area was selected based on soil type, vegetation type, elevation, and absence of cattle grazing and off-road vehicle use. Despite the difficulty of finding an exact reference area, the study results suggest that fences and culverts are effective, but signs are ineffective.
This report was accepted as Thesis in partial fulfillment of the requirements for the Masters of Science for Nani Bay Teves in Spring 2005.
June 2005.
Keywords: Forest management -- Colorado; Watershed management -- Colorado